2021
DOI: 10.1093/treephys/tpab058
|View full text |Cite
|
Sign up to set email alerts
|

Distinct morpho-physiological and biochemical features of arid and hyper-arid ecotypes of Ziziphus nummularia under drought suggest its higher tolerance compared with semi-arid ecotype

Abstract: Tree species in the arid and semi-arid regions use various strategies to combat drought stress. Ziziphus nummularia, native to the Thar Desert in India, is highly drought-tolerant. To identify the most drought-tolerant ecotype of Z. nummularia, one ecotype each from semi-arid (Godhra, annual rainfall > 750 mm), arid (Bikaner, 250–350 mm) and hyper-arid (Jaisalmer, < 150 mm) regions was selected along with two other Ziziphus species; Z. mauritiana and Z. rotundifolia, and screened for parameters c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The species Ziziphus nummularia (Burm.f.) Wight & Arn is highly draught tolerant and can survive in harsh conditions [29]. The species Prosopis juliflora (Swartz) DC.…”
Section: Discussionmentioning
confidence: 99%
“…The species Ziziphus nummularia (Burm.f.) Wight & Arn is highly draught tolerant and can survive in harsh conditions [29]. The species Prosopis juliflora (Swartz) DC.…”
Section: Discussionmentioning
confidence: 99%
“…Sivalingam et al [53] screened the parameters contributing to drought tolerance by comparing three Ziziphus nummularia ecotypes from semi-arid, arid and hyper-arid regions. Results showed that the latter was the most drought-tolerant ecotype and was associated with an increase in root length and number, an increase in leaf hair growth, and in elongation of thorns.…”
Section: Anti-drought and Anti-thermal Characteristics Of Ziziphus Nu...mentioning
confidence: 99%
“…In order to maintain a high relative water content for longer periods of time, membrane permeability was increased, and proline, catalase and sugar content was higher. Transcriptome profiling showed that genes associated with drought response mechanisms were constitutively expressed at higher levels [53].…”
Section: Anti-drought and Anti-thermal Characteristics Of Ziziphus Nu...mentioning
confidence: 99%